Nivolumab‐associated myositis myocarditis and myasthenia and anti‐striated muscle antibodies. Issue 8 (6th August 2020) - Fazal, Marium; Prentice, David A.; Kho, Lay K.; Fysh, Edward
Abstract: An 82‐year‐old man was treated with neo‐adjuvant nivolumab (programmed cell death protein 1 or PD‐1 inhibitor) for local recurrence of melanoma developed myositis, myocarditis and a myasthenic‐like syndrome with a fatal outcome. The occurrence of these three conditions may constitute a new immune checkpoint‐induced syndrome. The relevance of the clinical features and the immunology is discussed. This case highlights the special role of anti‐striated muscle antibodies as a predictor of mortality.